Effects of gallic acid and quercetin on the structural, thermal, spectroscopic, in vitro biocompatibility and electronic properties of Au-based hydroxyapatite structure - Keser, Serhat; Dogan, Ahmet; Ates, Tankut; Barzinjy, Azeez A.; Ates, Burhan; Tekin, Suat; Kaygili, Omer (Elsevier Science Sa, 2024)
The aim of this study is investigating the structural, thermal, spectroscopic, electronic and biocompatibility properties of the Au-based hydroxyapatites containing quercetin (Q) or gallic acid (GA) at various concentration. Different characterization techniques including; XRD analysis, FTIR and Raman spectroscopies, differential thermal analysis, SEM and EDX analysis were utilized. Cell cytotoxicity test was conducted with the cells of MG63 human bone cancer, hFOB 1.19 human osteoblast and Caco-2 human colon cancer. It has been shown that the utilized samples had no cytotoxic activity on the L-929, hFOB 1.19 and MG-63 cells. However, these samples had cytotoxic activity on Caco-2. The current study showed that the bandgap of the un-doped HAp structure was 4.976 eV. The crystallite size is also affected by Au-doping, type of the as-used biological additive and its amount. Also, the as-produced samples were thermally stable in the range from room temperature to 1000 degrees C. The particle size distributions of the samples were found at variable ranges. The molar ratios were close to the stoichiometric value of 1.667. These novel findings not only expand our appreciation for the role of dopants in materials science but also opens avenues for deliberate engineering of electronic properties for enhanced performance in various applications.
Keywords: Hydroxyapatite; Gold (Au); Quercetin; Gallic acid; Bandgap; X-ray diffraction (XRD)